Photosynthetic limitations in leaves of arabic coffee promoted by the water deficit - Peloso, Anelisa Figueiredo; Tatagiba, Sandro Dan; Reis, Edvaldo Fialho; Pezzopane, José Eduardo Macedo; Amaral, José Francisco Teixeira (Coffee Science - ISSN 1984-3909, 2017)
The objective of this study was to investigate the photosynthetic limitations in leaves of Coffea arabica, Catuaí Vermelho (IAC 144), subjected to water deficit, using this, the parameters of gas exchange photosynthesis [net CO2 assimilation rate(A), stomatal conductance (gs), transpiration rate (E) and internal CO2 concentration (Ci)], the chlorophyll fluorescence a parameters minimal fluorescence (F0), maximum fluorescence (Fm), maximum quantum efficiency of photosystem II (Fv/Fm), yield of photochemical [Y(II)], yield of regulated energy dissipation [Y(NPQ)] and yield of non-regulated dissipation losses [Y(NO)] as well as on the concentrations of chloroplastidic pigments and the electrolyte leakage (EE) in leaves plants grown at 30, 60 and 100% of water available (WA) on the substrate. According to the results it was found that the water deficit affected photosynthesis of plants, either through lower efficiency of energy use by the photochemical apparatus, and by significant decreases obtained in gs, which were associated with the decrease in the amounts of A. Reduction in Y(II) and increases in Y(NPQ) and Y(NO) have been associated with water deficit, suggesting that there was a decrease in the electron transport rate, leading to less use of light energy for photochemical. Interestingly, the F0 values Fm and Fv/Fm were not associated with the loss of photochemical function, chlorophylls and cell damage caused by the intensification of the water deficit.